FEATURES OF MANAGEMENT OF PREGNANT WOMEN WITH FETOPLACENTAL DISORDERS - Babakhanova A.M., Khamdamova D.S., Dauletova M.J. (Miasto Przyszłości, 2023)
Fetoplacental insufficiency in presence of arterial hypertension (AH) is the most common disease complicating the course of pregnancy, as well as one of the most pressing problems of medical science and practice [1,2,5,9,11]. In recentyears, pregnancy-related complications, including hypertensivedisorders, have increased in all economically developed countries, which is reflected in the latest publications [2,4,5,8].